ANALISIS BRAND MANTRA DI JEJARING HOTEL GRUP LOKAL TERHADAP INTERAKSI PELANGGAN DENGAN STUDI KASUS: FAVEHOTEL - Hari Iskandar (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
This research is all about studying the aims and explain also determine the influence of Brand Mantra on the local Hotel Group network on customer interaction, Case Study: Fave Hotel. Researcher would like to know about is there any impact about brand mantra with the customer interaction at favehotel. All data in this study were obtained through a questionnaire and using quantitative method. The sample of this study was 85 respondents who were customers of the Fave Hotel. Researcher used T-test, F-test, analysis of linier regression. Result from T-test for communicate dimension resulted tcalculate 29,729 > ttabel 1,9866 with significance 0,000<0,05, so concluded H11 accepted and H01 rejected means communicate has significant impact to customer interaction. Simplify dimension has tcalculate 36,619> ttabel 1,9866 with significance 0,000<0,005, so concluded H12 accepted and H02 rejected means simplify dimension has significant to customer interaction. Inspire dimension has tcalculdate 39,534 > ttabel 1,9866 with significance 0,000<0,05, so concluded H13 accepted and H03 rejected means inspire dimension has significant impact to customer interaction. F-test resulted with 57,302 > Ftabel 2,718 with significance 0,000 < 0,05 means brand mantra has significant impact to customer interaction. From regresion linier, Customer interaction (Y) = 25,104+ 0,197 (communicate)+0,373 (simplify) +2,745 (inspire) +4,108. Keywords: Brand Mantra, Communicate, Simplify, Inspire, customer interaction